AUGMENTED REALITY SEBAGAI MEDIA PENDIDIKAN KESEHATAN UNTUK ANAK USIA SEKOLAH - Yolinda Suciliyana; La Ode Abdul Rahman (Jurnal Surya Muda, 2020)
Technology in the multimedia field that is currently developing is Augmented Reality (AR). Utilization of Augmented Reality as a medium for children's education provides a new perspective on the existing educational media, not only using real objects but also using virtual objects in the delivery of information. AR is a technology that combines three-dimensional virtual objects into a real three-dimensional environment and displays them in real time. AR can make delivery easier and make information more interesting especially for children. AR is expected to be able to support as one of the media for school-age children in an effort to realize health promotion. This research method uses a literature review that focuses on the use of Augmented Reality as a medium for health education for school-age children. The literature used is in the form of articles originating from national and international journals. The application of AR as an educational medium can increase children's knowledge. In Indonesia the use of AR media has not been implemented much less especially in nursing. The need for the development of this AR media in the world of nursing.